Primary prevention of snakebite envenoming in resource-limited settings: A narrative review - Godpower Chinedu Michael; Ibrahim Aliyu; Bukar Alhaji Grema (Wolters Kluwer Medknow Publications, 2019)
Background: Snakebite envenoming is a neglected tropical disease that accounts for preventable morbidity and mortality, especially in resource-limited settings. This review aimed at examining the snake and human behaviors that facilitate snake-human encounters and highlighting the primary preventive measures for snakebite and the resultant envenoming. Materials and Methods: Google Scholar, Medline (via PubMed), and African Journal Online were searched from January 1959 to April 2019 for peer-reviewed studies addressing primary prevention of snakebite. We extended our search to grey literature from conference proceedings, documents from organizations, book chapters, and thesis. Results: We found few studies in medical literature on community knowledge of the intrinsic characteristics of snakes (e.g., its unique venom apparatus for nutrition, defense and competition, and its habitat and activities); however, there is appreciable amount of studies on human activities associated with snakebite envenoming. Deservedly, more studies appear to focus on snakebite management (secondary and tertiary prevention) with inadequate emphasis on primary prevention of snakebite (which may be the only intervention in some resource-limited settings). Conclusion: Synergy of efforts toward improving community knowledge of human behaviors associated with snakebite and snake behaviors may generate appropriate environmental and behavioral responses to curtail human-snake encounters. Hence, intensive promotion of primary prevention may be a useful approach toward reducing snakebite burden in resource-limited settings.